Motivasi Berprestasi Siswa Sekolah Menengah Dalam Pendidikan Agama Islam di Nisam, Aceh Utara - Najmul Ula (DAYAH: Journal of Islamic Education, 2019)
Motivation is an important factor in improving the achievement of high school students in Islamic religious education. Due to the motivation to achieve greatness, it will foster the spirit of learning for students. The purpose of this study to determine how the motivation of high school students' achievement in Islamic education in Nisam District, North Aceh regency. This research uses a qualitative approach with a multi site design study. Subjects of research data are students, principals, vice-principals, and teachers. Data were obtained by a nonprobability sampling technique with an in-depth interview and documentation research instrument. Data were analyzed by data reduction technique, data presentation, and verification. To measure the validity of data using credibility standards, dependability, and confirmability. The results showed that students of SMP Negeri 1 Nisam and SMP Negeri 3 Nisam experienced increased learning achievement and high learning spirit. With an indicator that students are already motivated to study and school with a passion. Achievement motivation succeeded in improving student achievement da spirit of learning activities toward the desired goal of students has achieved a goal that materialized.